Problems of students in memorizing the Quran in Islamic boarding school in Koto Kampar Hulu District - Asmardi Asmardi; Hasrian Rudi (Lembaga Riset Mutiara Akbar, 2026)
This study examines the challenges faced by students (santri) in memorizing the Qur’an in Islamic boarding schools (pesantren) in Koto Kampar Hulu District. Using a qualitative approach, data were collected through interviews, observations, and documentation involving santri, tahfizh teachers, and pesantren administrators. The findings indicate that students experience both internal and external obstacles in the memorization process. Internal challenges include limited mastery of makharijul huruf and tajwid, lack of consistency (istiqamah), insufficient practice of muraja’ah, difficulties in memorizing long and mutasyabihat verses, and rapid forgetting of previously memorized passages. External factors consist of learning environment conditions, mentoring patterns, and varying levels of parental support. To address these challenges, pesantren implement several strategies, such as routine muraja’ah, grouping students based on memorization ability, strengthening learning motivation, and involving parents in supporting the memorization process. The study concludes that consistency and regular repetition play a more decisive role in successful Qur’anic memorization than intellectual ability alone.